Remote control for a stand-alone freely movable treatment couch with limitation system - Van de Vondel, I; Coppens, L; Verellen, D; Linthout, N; Van Acker, S; Storme, G (Medical physics (Lancaster), 2001)
One of our linear accelerators is equipped with a free-movable treatment couch. An additional projects was to develop a system that first protects the free-movable couch against collisions, secondly build a remote control for moving the couch from outside the treatment room and finally implement this remote control/limitation system in an automatic position algorithm using an electronic portal image. The latter has been the subject of an on-going departmental investigation on intra-fractional correction of set-up errors. A few years ago, we developed a limitation system to protect both the table and the accelerator against collisions. In this paper we describe the second part of this project, the remote control system.